Average models for calculating the shock equation of state of alloy and mixture. (5th June 2019) - Young, G.; Lin, Xun; Leng, Chunwei; Huang, Haijun
Abstract: Accurate models for calculating the Hugoniot of a mixture and alloy are necessary in shock wave experiments. An average model modified from the isothermal averaging method is proposed to determine the shock equation of state for more than two-phase mixtures and alloys. Additionally, different average models are compared with the available experimental data, and the results show that the predicted shock Hugoniot by the modified isothermal averaging method has good agreement with the experimental data. The modified isothermal averaging method is completely flexible allowing for multi-component alloys and mixtures.